Chemical inhibition of the mitochondrial division dynamin reveals its role in Bax/Bak-dependent mitochondrial outer membrane permeabilization - Cassidy-Stone, Ann (2008)
Mitochondrial fusion and division play important roles in the regulation of apoptosis. Mitochondrial fusion proteins attenuate apoptosis by inhibiting release of cytochrome c from mitochondria, in part by controlling cristae structures. Mitochondrial division promotes apoptosis by an unknown mechanism. We addressed how division proteins regulate apoptosis using inhibitors of mitochondrial division identified in a chemical screen. The most efficacious inhibitor, mdivi-1 (for mitochondrial division inhibitor) attenuates mitochondrial division in yeast and mammalian cells by selectively inhibiting the mitochondrial division dynamin. In cells, mdivi-1 retards apoptosis by inhibiting mitochondrial outer membrane permeabilization. In vitro, mdivi-1 potently blocks Bid-activated Bax/Bak-dependent cytochrome c release from mitochondria. These data indicate the mitochondrial division dynamin directly regulates mitochondrial outer membrane permeabilization independent of Drp1-mediated division. Our findings raise the interesting possibility that mdivi-1 represents a novel class of therapeutics for stroke, myocardial infarction, and neurodegenerative diseases.